2008
DOI: 10.1021/jp709591e
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Reflection−Absorption Spectroscopy and Polarization-Modulated Infrared Reflection−Absorption Spectroscopy Studies of the Organophosphorus Acid Anhydrolase Langmuir Monolayer

Abstract: The secondary structure of the organophosphorus acid anhydrolase (OPAA) Langmuir monolayer in the absence and presence of diisopropylfluorophosphate (DFP) in the subphase was studied by infrared reflection-absorption spectroscopy (IRRAS) and polarization-modulated IRRAS (PM-IRRAS). The results of both the IRRAS and the PM-IRRAS indicated that the alpha-helix and the beta-sheet conformations in OPAA were parallel to the air-water interface at a surface pressure of 0 mN.m-1 in the absence of DFP in the subphase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The s-and p-polarized IRRAS results of the Langmuir monolayer of oganophosphorus acid anhydrolase (OPAA) are shown in Figure 3a and 3b, respectively [35]. OPAA contains most of the typical conformations (i.e., unstructured conformation, α-helix, β-sheet, turns and so on) as discussed above.…”
Section: Irras Of Example Proteinmentioning
confidence: 90%
See 3 more Smart Citations
“…The s-and p-polarized IRRAS results of the Langmuir monolayer of oganophosphorus acid anhydrolase (OPAA) are shown in Figure 3a and 3b, respectively [35]. OPAA contains most of the typical conformations (i.e., unstructured conformation, α-helix, β-sheet, turns and so on) as discussed above.…”
Section: Irras Of Example Proteinmentioning
confidence: 90%
“…Interestingly, the amide I band of unstructured conformation at 1640 cm -1 was not detected in p-polarized IRRAS. This result is reasonable because the carbonyls in unstructured conformation should be randomly distributed and this orientation is not preferred by p-polarized IRRAS, as discussed in the above section about the selection rules of IRRAS [35]. Similarly, some other proteins with high fraction of α-helix have been analyzed by IRRAS and important information about the change of both the conformation and orientation of the proteins has been addressed [35].…”
Section: Irras Of Example Proteinmentioning
confidence: 91%
See 2 more Smart Citations
“…, stability or aggregation) of amphiphile biomacromolecules at the air–water interface. 9-11 We recently observed that Aβ molecules accumulated at the air–water interface were predominantly present in the α-helical conformation. 9 A kinetic model was proposed to explain the Aβ adsorption behavior.…”
mentioning
confidence: 99%